Hemangiopericytoma/solitary fibrous tumor of the greater omentum: A case report and review of the literature. (2016) - Archid, Rami; Schneider, Carl Christoph; Adam, Patrick; Othman, Ahmed; Zieker, Derek; Königsrainer, Alfred
Highlights: Hemangiopericytoma is known to occur in any anatomical site, especially the extremities and retroperitoneum. Primary surgical resection is the treatment of choice. There is no benefit of radiation or systemic chemotherapy. Angiogenic inhibitors represent promising systemic therapeutic concepts for Hemangiopericytoma. Abstract: Introduction: Hemangiopericytoma (HPC) has been first described in 1942 by Stout as a tumor originating from the capillary surrounding pericytes. It is known to occur in any anatomical site, especially the extremities and retroperitoneum. Presentation of case: We describe a case of a 24 year old patient presenting with lower abdominal pain due to a tumor of the greater omentum, the patient was treated by conventional laparotomy with tumor resection and the histological evaluation confirmed the diagnosis Hemangiopericytoma/Solitary fibrous tumor (HPC/SFT). The patient has regularly followed-up with periodic imaging for the last 4 years, with no recurrences. Discussion and conclusion: According to our knowledge, HPC rarely develops in the greater omentum, only 20 cases were described in the literature. Primary surgical resection is the treatment of choice. There is no benefit of radiation or systemic chemotherapy. Angiogenic inhibitors represent promising systemic therapeutic concepts.